DNA methyltransferase candidate polymorphisms, imprinting methylation, and birth outcome. - Paul Haggarty; Gwen Hoad; Graham W Horgan; Doris M Campbell (PLoS ONE, 2013)
BACKGROUND: Birth weight and prematurity are important obstetric outcomes linked to lifelong health. We studied a large birth cohort to look for evidence of epigenetic involvement in birth outcomes. METHODS: We investigated the association between birth weight, length, placental weight and duration of gestation and four candidate variants in 1,236 mothers and 1,073 newborns; DNMT1 (rs2162560), DNMT3A (rs734693), DNMT3B (rs2424913) and DNMT3L (rs7354779). We measured methylation of LINE1 and the imprinted genes, PEG3, SNRPN, and IGF2, in cord blood. RESULTS: The minor DNMT3L allele in the baby was associated with higher birth weight (+54 95% CI 10,99 g; p = 0.016), birth length (+0.23 95% CI 0.04,0.42 cm; p = 0.017), placental weight, (+18 95% CI 3,33 g; p = 0.017), and reduced risk of being in the lowest birth weight decile (p = 0.018) or requiring neonatal care (p = 0.039). The DNMT3B minor allele in the mother was associated with an increased risk of prematurity (p = 0.001). Placental size was related to PEG3 (p<0.001) and IGF2 (p<0.001) methylation. Birth weight was related to LINE1 and IGF2 methylation but only at p = 0.052. The risk of requiring neonatal treatment was related to LINE1 (p = 0.010) and SNRPN (p = 0.001) methylation. PEG3 methylation was influenced by baby DNMT3A genotype (p = 0.012) and LINE1 by baby 3B genotype (p = 0.044). Maternal DNMT3L genotype was related to IGF2 methylation in the cord blood but this effect was only seen in carriers of the minor frequency allele (p = 0.050). CONCLUSIONS: The results here suggest that epigenetic processes are linked birth outcome and health in early life. Our emerging understanding of the role of epigenetics in health and biological function across the lifecourse suggests that these early epigenetic events could have longer term implications.